2015
DOI: 10.1371/journal.pone.0122523
|View full text |Cite
|
Sign up to set email alerts
|

Is Having Sex with Other Men a Risk Factor for Transfusion-Transmissible Infections in Male Blood Donors in Western Countries? A Systematic Review

Abstract: BackgroundAlthough increased prevalence of transfusion transmissible infections (TTI) among “men who have sex with men” (MSM) has been well documented, the exclusion of MSM as blood donors is contested. The aim of this systematic review is to find studies that describe the risk of TTI in MSM blood donors.MethodsWe searched MEDLINE, Embase, The Cochrane Central Register of Controlled Trials, Cinahl, and Web of Science, and used GRADE for determining evidence quality. We included studies comparing MSM and non-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 32 publications
(86 reference statements)
0
36
0
Order By: Relevance
“…It is noteworthy that donors' opinion about screening policies might have been influenced by the level of public awareness and advocacy around the MSM deferral policy. The MSM donor deferral policy in many countries has been debated for years . Previous studies found that donors may not find DHQ questions acceptable due to misunderstanding of the risk of sexual behavior on blood safety and perception of unfair screening .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that donors' opinion about screening policies might have been influenced by the level of public awareness and advocacy around the MSM deferral policy. The MSM donor deferral policy in many countries has been debated for years . Previous studies found that donors may not find DHQ questions acceptable due to misunderstanding of the risk of sexual behavior on blood safety and perception of unfair screening .…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen low-quality observational studies suggested a link between blood donors who were MSM and HIV-1 infection, but the evidence is too limited to recommend a precise deferral period. 31 Recently, a systematic review was performed on the risk of TTIs in blood donors who recently had an endoscopic examination, since the invasive procedure and the reusable character of an endoscope could threaten a safe blood supply. Twenty-eight observational studies (of very low quality) were included, and several meta-analyses showed an association between endoscopic examinations and hepatitis B and C infection.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Because of this tragic history, decision makers may decide that a potential--though sometimes theoretical--risk must not be taken and that actions are determined accordingly [17]. It is sometimes difficult to decipher between an actual and a theoretical epidemiological risk where expected occurrence is extremely low: this has typically been the case for the ban from donating blood of males having or having had sexual intercourse with other men [18]. The societal dispute between blood transfusion professionals and nonprofessionals often focuses on the issues of theory (principle of precaution) vs epidemiology (actual data).…”
Section: The Drivers Of the Precautionary Principle In Transfusionmentioning
confidence: 99%